2015
DOI: 10.1021/es5047155
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Transformation of Graphene Oxide in Sunlight

Abstract: Graphene oxide (GO) is promising in scalable production and has useful properties that include semiconducting behavior, catalytic reactivity, and aqueous dispersibility. In this study, we investigated the photochemical fate of GO under environmentally relevant sunlight conditions. The results indicate that GO readily photoreacts under simulated sunlight with the potential involvement of electron-hole pair creation. GO was shown to photodisproportionate to CO2, reduced materials similar to reduced GO (rGO) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
161
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(171 citation statements)
references
References 48 publications
9
161
0
1
Order By: Relevance
“…To date, only a few studies have focused on the transformation of GO in conditions similar and/or relevant to the natural environment Feng et al, 2015;Hou et al, 2015Hou et al, , 2016. Some of these studies have shown that sunlight is able to induce some physicochemical changes to the nanomaterials when present in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few studies have focused on the transformation of GO in conditions similar and/or relevant to the natural environment Feng et al, 2015;Hou et al, 2015Hou et al, , 2016. Some of these studies have shown that sunlight is able to induce some physicochemical changes to the nanomaterials when present in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent or subsequent sunlight irradiation of chlorinated GO may result in further transformation, affecting further the physicochemical properties (and thus, environmental implications) of GO. This potential transformation of GO by photochlorination has not received much attention as most existing studies on the environmental fate of GO focused on its colloidal stability and sunlightinduced transformations (Chowdhury et al, 2013Wu et al, 2013;Hou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…46 However, the experimental evidences have shown a reverse behaviour. Interestingly, sRGO has showed enhanced conductivity compared to RGO samples prepared through other routes.…”
mentioning
confidence: 99%
“…If this potential can then be coupled with the digitization and real-time monitoring of the cell sample (microdroplets), GO could be clinically exploited in the very near future. In our humble opinion, the great expectations fueling graphene-based research warrant a "digital shotgun" approach, thus clarifying any doubts regarding its efficacy and applicability not just in nanomedicine, but its future impact on environmental 181 and public health.…”
Section: Resultsmentioning
confidence: 98%